EXPERT SYSTEM TO DETERMINE THE DISEASE OF GUPPY ORNAMENTAL FISH USING FORWARD CHAINING METHOD - Vicky Fachrozy (Bahasa Indonesia, 2023)
The development of the world of technology is growing according to human development. The development of information technology affects many fields such as education, livestock industry, health and has a positive impact on us. The impact in aquaculture is that it makes it easier for us to find and process the information we need wherever we are, by using an easy way we can get information. The expert system itself is a system to make it easier to find information and solutions to existing problems, this expert system is designed to facilitate and assist guppy ornamental fish cultivators in finding solutions to disease problems using algorithms and methods, one of which is the forward chain method. Guppy fish (Poecilia reticulata) is an ornamental fish that has high commercial value in both domestic and foreign markets. In the business of guppy ornamental fish cultivation, disease in fish is the biggest risk experienced by guppy ornamental fish cultivators. The application or development of an expert system using the forward chaining method in this study because it will be created or built requires data input from the user and requires an approach.